Numerical Experiments for Nuclear Flashes toward Superbursts in an Accreting Neutron Star. (23rd July 2014) - Hashimoto, Masa-aki; Kuromizu, Reiko; Ono, Masaomi; Noda, Tsuneo; Fujimoto, Masayuki Y.
Abstract : We show that the superburst would be originated from thermonuclear burning ignited by accumulated fuels in the deep layers compared to normal X-ray bursts. Two cases are investigated for models related to superbursts by following thermal evolution of a realistic neutron star: helium flash and carbon flash accompanied with many normal bursts. For a helium flash, the burst shows the long duration when the accretion rate is low compared with the observation. The flash could become a superburst if the burning develops to the deflagration and/or detonation. For a carbon flash accompanied with many normal bursts, after successive 2786 normal bursts during 1.81 × 10 9 s, the temperature reaches the deflagration temperature. This is due to the produced carbon which amount reaches to ≈0.1 in the mass fraction. The flash will develop to dynamical phenomena of the deflagration and/or detonation, which may lead to a superburst.